Evaluation of miscellaneous and electronic device energy use in hospitals. (1st January 2013) - Black, Douglas R.; Lanzisera, Steven M.; Lai, Judy; Brown, Richard E.; Singer, Brett C.
Miscellaneous and electronic loads (MELs) consume about one-third of the primary energy used in US buildings, and their energy use is increasing faster than other end-uses. In healthcare facilities, 30% of the annual electricity was used by MELs in 2008. This paper presents methods and challenges for estimating medical MELs energy consumption along with estimates of energy use in a hospital by combining device-level metered data with inventories and usage information. An important finding is that common, small devices consume large amounts of energy in aggregate and should not be ignored when trying to address hospital energy use.